Chemical modification allows phallotoxins and amatoxins to be used as tools in cell biology - Anderl, Jan; Echner, Hartmut; Faulstich, Heinz (Beilstein Journal of Organic Chemistry, 2012)
Phallotoxins inhibit the dynamics of microfilaments in cells and lead to apoptosis. Due to poor cellular uptake these effects cannot be studied in live cells, even at millimolar toxin concentrations, nor can phalloidin be used for the elimination of tumor cells. Uptake is greatly enhanced by conjugation of phallotoxins to either lipophilic or polycationic moieties, such as oleic acid, polylysine, or Tat-peptide. These conjugates were lethally toxic for cells, e.g., mouse fibroblasts or Jurkat leukemia cells, in the micromolar range. Uptake into cells starts with the attachment of the toxin conjugates to the plasma membrane, followed by endocytosis and, in most cases, cleavage of the toxin from the carrier. Interestingly, the internalization rate of phalloidin into cells was also significantly increased by the fluorescent moiety tetramethylrhodaminyl, as well as by high molecular weight methoxy-polyethyleneglycol, two compounds unknown so far for their uptake-mediating activity. Conjugation to carriers as investigated in this work will allow the use of phallotoxins in experimental cell biology and possibly in tumor therapy. The findings obtained with phallotoxins could be applied also to the family of amatoxins, where α-amanitin, for example, when conjugated to oleic acid was more than 100-fold more toxic for cells than the native toxin. This suggests the possibility of a more general use of the moieties examined here to enhance the uptake of hydrophilic peptides, or drugs, into live cells.
Keywords: amatoxins; cellular uptake; endocytosis; peptides; phalloidin; phallotoxins